The ecology of pelagic freshwater methylotrophs assessed by a high-resolution monitoring and isolation campaign - Salcher, Michaela M; Neuenschwander, Stefan M; Posch, Thomas; Pernthaler, Jakob (The ISME journal, 2015)
Methylotrophic planktonic bacteria fulfill a particular role in the carbon cycle of lakes via the turnover of single-carbon compounds. We studied two planktonic freshwater lineages (LD28 and PRD01a001B) affiliated with Methylophilaceae (Betaproteobacteria) in Lake Zurich, Switzerland, by a combination of molecular and cultivation-based approaches. Their spatio-temporal distribution was monitored at high resolution (n=992 samples) for 4 consecutive years. LD28 methylotrophs constituted up to 11 × 10(7) cells l(-1) with pronounced peaks in spring and autumn-winter, concomitant with blooms of primary producers. They were rare in the warm water layers during summer but abundant in the cold hypolimnion, hinting at psychrophilic growth. Members of the PRD01a001B lineage were generally less abundant but also had maxima in spring. More than 120 axenic strains from these so far uncultivated lineages were isolated from the pelagic zone by dilution to extinction. Phylogenetic analysis separated isolates into two distinct genotypes. Isolates grew slowly (μmax=0.4 d(-1)), were of conspicuously small size, and were indeed psychrophilic, with higher growth yield at low temperatures. Growth was enhanced upon addition of methanol and methylamine to sterile lake water. Genomic analyses of two strains confirmed a methylotrophic lifestyle with a reduced set of genes involved in C1 metabolism. The very small and streamlined genomes (1.36 and 1.75 Mb) shared several pathways with the marine OM43 lineage. As the closest described taxa (Methylotenera sp.) are only distantly related to either set of isolates, we propose a new genus with two species, that is, 'Candidatus Methylopumilus planktonicus' (LD28) and 'Candidatus Methylopumilus turicensis' (PRD01a001B).
Keywords: genom bakteriální; methanol; DNA bakterií; Ecology; DNA, Ribosomal; Phylogeny; Likelihood Functions; Sequence Analysis, DNA; Carbon Cycle; Water Microbiology; nízká teplota; RNA ribozomální 16S; Genotype; Lakes; Švýcarsko; RNA, Ribosomal, 16S; Cold Temperature; reprodukovatelnost výsledků; jezera; sladká voda; sekvenční analýza DNA; DNA, Bacterial; roční období; Fresh Water; Reproducibility of Results; fylogeneze; Seasons; Switzerland; koloběh uhlíku; Methanol; Betaproteobacteria; ribozomální DNA; plankton; genotyp; pravděpodobnostní funkce; mikrobiologie vody; ekologie; Genome, Bacterial; Plankton; Methylophilaceae